Free Cysteine Modulates the Conformation of Human C/EBP Homologous Protein - Singh, Vinay K. (Public Library of Science, 2012)
The C/EBP Homologous Protein (CHOP) is a nuclear protein that is integral to the unfolded protein response culminating from endoplasmic reticulum stress. Previously, CHOP was shown to comprise extensive disordered regions and to self-associate in solution. In the current study, the intrinsically disordered nature of this protein was characterized further by comprehensive in silico analyses. Using circular dichroism, differential scanning calorimetry and nuclear magnetic resonance, we investigated the global conformation and secondary structure of CHOP and demonstrated, for the first time, that conformational changes in this protein can be induced by the free amino acid l-cysteine. Addition of l-cysteine caused a significant dose-dependent decrease in the protein helicity – dropping from 69.1% to 23.8% in the presence of 1 mM of l-cysteine – and a sequential transition to a more disordered state, unlike that caused by thermal denaturation. Furthermore, the presence of small amounts of free amino acid (80 µM, an 8∶1 cysteine∶CHOP ratio) during CHOP thermal denaturation altered the molecular mechanism of its melting process, leading to a complex, multi-step transition. On the other hand, high levels (4 mM) of free l-cysteine seemed to cause a complete loss of rigid cooperatively melting structure. These results suggested a potential regulatory function of l-cysteine which may lead to changes in global conformation of CHOP in response to the cellular redox state and/or endoplasmic reticulum stress.